Efficacy of oral citrulline supplementation to decrease the risk of pulmonary hypertension after congenital heart disease surgery: A local experience - Silvera Ruiz, Silene Maite (2020)
Pulmonary hypertension (PH) is a major cause of morbi-mortality among patients with congenital heart disease (CHD) and also a potentially severe complication after surgical repair. Oral citrulline, a precursor to NO synthesis, is safe and efficacious for decreasing the risk of postoperative PH. Objective: The aim of the present study was to investigate in pediatric patients the changes of plasma citrulline, arginine, homocysteine and nitric oxide (NO) metabolites and pulmonary artery pressures (PAP) pre-post cardiac surgery in order to describe our population status with regard to the risk of pulmonary hypertension and look for potential biomarkers for early detection and treatment. Main results/Discussion: 16 Argentine pediatric patients with CHD undergoing cardiopulmonary bypass were randomized in two groups: (A) with and (B) without perioperative citrulline supplementation. We found that plasma citrulline median levels before surgery were lower in both groups respect to referential values, probably due to the poor nutritional status of our patients; only group A surpassed post-surgery the minimum recommended level to avoid PH. Furthermore, none of the patients in group A showed mean PAP higher than 20 mmHg, whereas in group B, 67% of the measurements were ≥ than the reference level. Conclusions: We reaffirm that citrulline supplementation it is effective in reducing postoperative pulmonary hypertension and biomarkers could evidence patient status as a translational medicine application.